Evaluation of a gene signature related to thrombotic manifestations in antiphospholipid syndrome - Jacintho, Bruna Cardoso; Mazetto Fonseca, Bruna de Moraes; Hounkpe, Bidossessi Wilfried; Oliveira, Jose Diogo; dos Santos, Ana Paula Rosa; Vaz, Camila de Oliveira; de Paula, Erich Vinicius; Orsi, Fernanda Andrade (Frontiers in Medicine, 2023)
Thrombotic primary antiphospholipid syndrome (t-PAPS) is an acquired condition characterized by heterogeneous thrombotic manifestations, which is intriguing since venous and arterial thrombosis appear to have distinct pathogenesis. Gene expression analysis may constitute a new approach to evaluate potential similarities or differences between the clinical manifestations of t-PAPS. Recently, dysregulation of the ANXA3, TNFAIP6, TXK, BACH2 and SERPINB2 genes has been associated with both arterial and venous thrombosis in the general population. Therefore, the aim of this study was to examine whether ANXA3, TNFAIP6, TXK, BACH2 and SERPINB2 expression was associated with t-PAPS. Gene expression was quantified by qPCR of total leukocyte mRNA. In this case-control study, 100 t-PAPS patients, 17 asymptomatic antiphospholipid (aPL) carriers and 100 controls were evaluated. Increased expression of ANXA3 (P=0.008) and TNFAIP6 (P=0.001) and decreased expression of the TXK gene (P=0.0001) were associated with an increased risk of t-PAPS compared to the control. ANXA3 upregulation was more evident in cases of arterial thrombosis and multiple thrombotic events. There was no difference in the expression of these genes between triple and nontriple aPL positivity. ANXA3, TNFAIP6, TXK, BACH2 and SERPINB2 expression levels were also similar between aPL carriers and controls (P= 0.77; P= 0.48; P=0.08; P=0.73 and P=0.13, respectively). In conclusion, our results showed that genes related to hemostasis (ANXA3) and immunity (TNFAIP6, TXK) are dysregulated in t-PAPS compared to controls. Gene dysregulation was not detected in aPL carriers and was not related to the aPL profile, suggesting that this gene signature is related to thrombotic manifestations rather than to aPL burden. Our results suggest that innate immunity and hemostasis pathways are associated with t-PAPS at a molecular level and may play a role in disease severity.